THE IMPACT OF PHET-ASSISTED EXPERIMENTAL LEARNING METHODS ON STUDENTS' SCIENCE PROCESS SKILLS IN SCIENCE TOPICS - Alissa Nazilatur Rohmah; Kiki Septaria; Agus Santoso (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
The focus of this study is to find out how the PhET-assisted experiential learning technique affects students' Science Process Skills on energy-related material. A quantitative technique was applied in the research design, which was one group pretest posttest. This study will take place in SMP N 1 Sugio Lamongan. Purposive sampling was used in the sample selection process. There were 181 students in this study. The research included 66 students divided into two groups, class A and class B. However, data could not be gathered for 5 kids due to school activities, limiting the sample to 61 students. The insight gathering approach involves cognitive tests and observation of performance tests, followed by hypothesis evaluation with a paired simple t-test. The findings of this investigation show that learning using the PhET-assisted experimental approach to learning encounters a substantial impact on students' Science Process Skills in energy change material, with an average cognitive pretest score of 40.03, a posttest result of 78.95, and an N-gain value of 0.64, and obtained data from performance test observations with a pretest value of 35.65, a posttest result of 84.42, and an N-gain value of 0.75. The integration of experiential learning techniques aided by PhET has an impact on students' Science Process Skills, as evidenced by pretest posttest outcomes that have increased to the moderate level.